La disgrafía en el proceso de aprendizaje de los niños y niñas de segundo año de educación básica de la escuela “Nuestra Señora del Quinche” ubicada en la parroquia Ximena, cantón Guayaquil, provincia Guayas; período lectivo 2013 – 2014 - Jara Aguilar, Carmelina Victoria (2014)
Writing is an encoding process that humans do in an oral form. The teaching of the handwriting is the essential proper educational development of children. Learning abilities develop as you progress in your school and goes through three stages or phases: A pre- k, which develops in the first two years of initial education prepares the child to acquire graph motor control necessary for subsequent Writing: calligraphic phase, where teaching gets into the writing, also in the learning of the various graphics of the letters and their sequence, and the last stage of refinement, when a child consolidates previously acquired learning achieved personalize it and give it his own style. The progress of each child in the first two stages generally depends on the level of maturity he had acquire, that means, must have adequate intellectual level, have successfully developed of the language and have obtained the appropriate psychomotor skills. The present work is thus have as an aims to solve problems about learning that some children’s had been having at second grade on the Basic Education in our "Neustria Señora del Quinche School" located in the province of Guayas Canton Guayaquil, academic year 2013-2014.W Regarding written language such as: illegible handwriting or dysgraphia, which refers to the inability to produce a legibly handwriting, different sizes, and student does not respect the rows, poor body posture, and slow handwriting. As it is essential to develop the skills and abilities for the writing especially in the early years of school where children are more predisposed to get the learning process. And it shall be the responsibility of teachers to help the students to learn the way how to write correctly and develop fine motor skills by applying different techniques proposed for these skills. The main purpose of our research is to disseminate, why children have illegible handwriting or dysgraphia? And about why it is importance to use a correct process in the application of technical methods in the development of fine motor skills? In order to prevent this problem from early ages in early childhood education. The work structure has the problem statement, the sub problems, the subject, the objectives, hypothesis, independent and dependent variables, operationalization of variables. Chapter I, deals with the theoretical framework that is structured by four guidelines: the scientific theory that involves the investigation about different concepts of dysgraphia, educational causes, types of dysgraphia, dysgraphia classification, treatment for dysgraphia, concept of learning, stages of learning, learning styles, learning theories, learning styles. The conceptual theory refers to the new terms used in research. The referential theory was obtained from the school, the history of the school and the legal framework as the articles from the law of the education, which relates the theme that was used in the school. Chapter II which emphasis on the approaches applied to students who have gaps in calligraphy and affects the learning process, it is a research field, descriptive field, explanatory and diagnostic field. The application of different methods that helpful to us and the techniques applied to the teachers, parents and test basic functions that helped us was applied to detect the problems on presented learners in second grade and provide feedback at different difficulty that was observed. Chapter III, emphasizes on the results of surveys of parents, interviews with teachers and different techniques have been applied to students in order to test the hypothesis and provide conclusions and recommendations to the work performed. And. Chapter IV, where the proposed solution are given to the various problems presented by students during the learning process. At the end of it, there are annexes and the bibliography about this research work.